2013
DOI: 10.1139/apnm-2012-0342
|View full text |Cite
|
Sign up to set email alerts
|

Acute sodium ingestion has no effect on short-term food and water intake, subjective appetite, thirst, or glycemic response in healthy young men

Abstract: The high intake of dietary sodium (Na(+)) has been associated with obesity and insulin resistance, sparking the hypothesis that the consumption of salty foods affects food intake (FI) and postprandial blood glucose (BG) response. Therefore, we conducted 2 randomized repeated-measures experiments to examine the acute effects of the Na(+) content of solid food and beverage on FI, water intake (WI), subjective appetite, thirst, and BG. FI and WI were measured at ad libitum pizza test meals; appetite, thirst, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Some experimental studies in animals also agree with the results of our study [15,16]. However, a randomized repeated-measures experiment conducted among healthy young men showed that the acute intake of sodium did not affect thirst or water intake [39]. Another study in adult rats showed that 10 days of dietary sodium deficiency inversely increased water intake [40].…”
Section: Discussionsupporting
confidence: 88%
“…Some experimental studies in animals also agree with the results of our study [15,16]. However, a randomized repeated-measures experiment conducted among healthy young men showed that the acute intake of sodium did not affect thirst or water intake [39]. Another study in adult rats showed that 10 days of dietary sodium deficiency inversely increased water intake [40].…”
Section: Discussionsupporting
confidence: 88%